Prospective Evaluation of the Efficacy of Isolated Balloon Eustachian Tuboplasty: Short- and Medium-term Follow-up Results Based on Tubomanometry, ETDQ-7, Tympanometry, and Valsalva Maneuver - Cátia Azevedo; Filipa Moreira; António Fontes Lima; Fernando Milhazes Mar; Sérgio Vilarinho; Luís Dias (International Archives of Otorhinolaryngology, 2024)
Introduction Balloon eustachian tuboplasty (BET) allows the treatment of the main etiology of eustachian tube disfunction (ETD).